EFFECT OF rGH HORMONE ADMINISTRATION ON PROTEASE ENZYME ACTIVITY AND RNA/DNA RATIO OF STRIPED CATFISH (Pangasianodon hypophthalmus) MAINTAINED IN SALINE MEDIA - Syahputra, Mohamad Ardani; Tang, Usman M; Syawal, Henni (Asian Journal of Aquatic Sciences, 2024)
Striped catfish is a prevalent fish and is in great demand. Striped catfish cultivation generally uses fresh water as a living medium, but several freshwater fish commodities are starting to be developed to adapt to saline media. Harvesting striped catfish usually takes approximately 3 - 8 months. To overcome this, one way is to use growth hormone. The growth hormone currently used is Recombinant Growth Hormone (rGH). GH administration has been reported to have various effects, particularly on protein metabolism. In fish digestion, protein from feed cannot be directly absorbed but is first broken down by protease enzymes into amino acids. The physical appearance, which is the phenotype of an organism, is the result of metabolic processes in each cell that makes up the organism. This research aimed to analyze the effect of administering the rGH hormone on protease enzyme activity, RNA/DNA ratio, and growth of striped catfish maintained in saline media. The method used was experimental in the form of a Completely Randomized Design (CRD) with four treatments and three replications. Based on the results obtained during the research, it shows that Protease Enzyme Activity (U/minute) and the best RNA/DNA Ratio use a dose of 3 mg/kg with respective values ​​of 0.75±0.24 U/minute and3.30±0.49.